The ‘New Enemet’: Politics of Religion in Indonesia and The Impact on Contemporary Artistic Practies - Adelina Luft (Universitas Gadjah Mada, 2017)
The present paper wishes to investigate the relation between the politics of religion and the consequent effects on the contemporary art practices in Indonesia during the last decade. By looking at two major cases:Christanto’s exhibition in 2002 and “Pinkswing Park” from 2005 CP Biennale, the article takes an incursion into the relations between religion and politics by looking at how and in what ways the Islamic extremist groups can influence and restrict freedom of expression in a democratic country. I argue that the Islamic fundamentalists are representing the new enemies in the current freedom of expression, after the previous eras which saw the presence of other enemies: the state and the military, affecting both the levels of nation policies, contemporary art world and the individual artistic practice.